2008
DOI: 10.1103/physrevlett.101.026802
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Metallic States at the Heterointerface between the Band InsulatorsLaAlO3andSrTiO3

Abstract: We have studied the electronic structure at the heterointerface between the band insulators LaAlO3 and SrTiO3 using in situ photoemission spectroscopy. Our experimental results clearly reveal the formation of a notched structure on the SrTiO3 side due to band bending at the metallic LaAlO3/TiO2-SrTiO3 interface. The structure, however, is absent at the insulating LaAlO3/SrO-SrTiO3 interface. The present results indicate that the metallic states originate not from the charge transfer through the interface on a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
124
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 23 publications
8
124
1
Order By: Relevance
“…The discovery of a 2DEG (ref. 3) at the heterointerface between band insulators LaAlO 3 (LAO) and SrTiO 3 (STO) has launched many experimental [2][3][4][5][6][7][8][9][10][11][12]16 and theoretical 13,17,18 investigations of the fundamental origins and properties of this novel electronic state. Thiel et al 7 reported non-volatile electrical control of a metal-insulator quantum phase transition in LAO/STO heterointerface at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of a 2DEG (ref. 3) at the heterointerface between band insulators LaAlO 3 (LAO) and SrTiO 3 (STO) has launched many experimental [2][3][4][5][6][7][8][9][10][11][12]16 and theoretical 13,17,18 investigations of the fundamental origins and properties of this novel electronic state. Thiel et al 7 reported non-volatile electrical control of a metal-insulator quantum phase transition in LAO/STO heterointerface at room temperature.…”
mentioning
confidence: 99%
“…H eterointerfaces between different oxide layers can display remarkable electrical properties 1 that differ from either constituent, such as a two-dimensional electron gas (2DEG, refs [2][3][4][5][6][7][8][9][10][11][12][13][14] and interfacial superconductivity 15 . The discovery of a 2DEG (ref.…”
mentioning
confidence: 99%
“…These data also suggest that many of the conflicting (and often contradictory) studies of this popular system can be explained by this observation, that is, whether measurements are made in situ 31 , or after various surface exposures (for example, atmospheric water, or solvent cleaning) [32][33][34] , the sensitive electronic structure of the interface may be dramatically altered. For example, the predicted electric field across the LaAlO 3 layer [18][19][20] was not observed in X-ray photoemission studies 32 that may be explained consistently because the surface adsorbates (in particular atmospheric water) induced by the ex-situ processing reduce V Uncom , or equally, the electrical field across the LaAlO 3 layer.…”
Section: Comparison Between Sap and Adsorption Of Solvent Vapourmentioning
confidence: 94%
“…The resulting bound charges would give rise to a finite electric field and confining potential at the interface. 27,46,47 This is analogous to the mechanism that gives rise to a confined electron gas in wide bandgap polar GaN (III-V) and ZnO (II-VI) based heterostructures. 3,4 Thus the weak polarity of the SrTiO 3 may also play an important role in determining the electrostatic boundary conditions at the LaAlO 3 /SrTiO 3 interface, in direct comparison with the polar semiconductors.…”
mentioning
confidence: 99%